Entrepreneurship in Innovation Communities Insights from 3D Printing Startups and the Dilemma of Open Source Hardware - Ferdinand, Jan-Peter (Contributions to Management Science,, 2018)
Drawing on empirical insights from the field of desktop 3D printing, this book elaborates the concept of innovation communities as a pattern of open and distributed innovation. As these communities spur a fruitful exchange of explorative, open source knowledge, they represent a novel mode of "doing innovation", which considerably differs from established practices in market and business realms. Hence, the people that participate in these collective endeavors often develop entrepreneurial ambitions and start to exploit community-based innovations commercially. The book presents deep insights on the institutional idiosyncrasies of innovation communities, the associated dilemma of entrepreneurship and the strategies of 3D-printing startups to face the corresponding challenges.